Hypoglycemic Effects of Extract Nigella Sativa in Diabetic mice model - Awwaliya, Evi; Salim, Hotimah Masdan; Muhammad, David Sajid; Romadhani, Deny Febriwijaya; Nisaussholihah, Nadia (Jurnal Medis Islam Internasional, 2019)
Background; Adiponectin is an important adipokine with anti-inflammatory and insulin-sensitizing effects, the circulating levels of which are reduced in individuals with type 2 diabetes and obesity. Indeed, there is evidence that adiponectin released from perivascular adipose tissue (PVAT), that may play a key role in vascular physiology, as bioactive molecules released from it could have direct paracrine effects on the underlying vessel. The present study investigated the effects of extract Nigella sativa (N. sativa) on blood glucose levels of diabetic mice. Materials; Eight-week-old male musmusculus were treated with alloxan (150 mg/ kg) by a single intraperitoneal injection to induce diabetes mellitus. At 3 days of injection, N. sativa extract (150 and 300 mg/kg) was administered via gavage for 2 weeks. Results: The extract of N.Sativa administration significantly reduced blood glucose level (P < 0.05). However, N.Sativa did not alter a body weight Conclusion: Extract of Nigella Sativa improved blood glucose level in diabetic mice model.